USE OF MULTIMEDIA TECHNOLOGIES TO ORGANIZE OPTIONAL CLASSES (Conference Zone, 2022)
This article substantiates the effectiveness of the use of multimedia technologies in the process of organizing extracurricular activities and extracurricular activities in the subject, developed a system of practical methods and techniques of work using multimedia technologies.